2010
DOI: 10.1007/s11095-010-0091-0
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide Delivery to Tumor Cells by a Multifunctional Nano Vehicle Based on Poly(β-L-malic acid)

Abstract: Purpose Temozolomide (TMZ) is a pro-drug releasing a DNA alkylating agent that is the most effective drug to treat glial tumors when combined with radiation. TMZ is toxic, and therapeutic dosages are limited by severe side effects. Targeted delivery is thus needed to improve efficiency and reduce non-tumor tissue toxicity. Methods Multifunctional targetable nanoconjugates of TMZ hydrazide were synthesized using poly(β-L-malic acid) platform, which contained a targeting monoclonal antibody to transferrin rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 33 publications
0
76
0
Order By: Relevance
“…6. The greater drug accumulation was due to the avoidance of the drug efflux pump mechanism via receptor-mediated endocytosis [111]. In addition to T98G, the human glioblastoma cell line U251 is known to have MDR due to the high expression of P-glycoprotein and other ABC transporters.…”
Section: Specific Resistance Mechanisms Overcome By Nanomedicinementioning
confidence: 99%
“…6. The greater drug accumulation was due to the avoidance of the drug efflux pump mechanism via receptor-mediated endocytosis [111]. In addition to T98G, the human glioblastoma cell line U251 is known to have MDR due to the high expression of P-glycoprotein and other ABC transporters.…”
Section: Specific Resistance Mechanisms Overcome By Nanomedicinementioning
confidence: 99%
“…56,57 Studies have shown that nanomedicines can overcome tumor chemoresistance to alkylating agents. [58][59][60] For example, temozolomide, a commonly used alkylating agent, is considered the gold standard for the treatment of glioblastoma. 61,62 However, growing resistance to temozolomide remains a major clinical challenge.…”
Section: Alkylating Agentsmentioning
confidence: 99%
“…60,65,66 Patil et al synthesized multifunctional temozolomide nanoconjugates (6.5-14.8 nm) using poly(β-l-malic acid), which contained trileucine (LLL) and antibody to transferrin receptor. 58 It was found that temozolomide-resistant cells were sensitive to the temozolomide nanoconjugates, 58 clearly demonstrating the feasibility of overcoming tumor cell resistance to the alkylating agent temozolomide by formulating it into nanomedicine.…”
Section: Alkylating Agentsmentioning
confidence: 99%
“…The multifunctionality of nanopolymers bearing various antisense oligonucleotides has been demonstrated by highly efficient treatment of glioblastoma [11], HER2 + [12] and triple- negative [13] breast tumors in vivo, and with temozolomide treatment of brain cancer cells in vitro [14]. …”
Section: Nanopolymers For Personalized Therapymentioning
confidence: 99%